Numerical Simulation of the Effect of Leading-edge Tubercles on the Hydrodynamic Performance of Hydrofoils at Low and High Reynolds Numbers - Johnson, Peter (Curtin University, 2018)
The tubercles on the pectoral flippers of humpback whales are thought to give superior manoeuvrability to these marine mammals. Numerical simulation of the flow over hydrofoils with and without leading-edge tubercles were conducted to test the protuberances’ effect on the hydrofoils hydrodynamic performance. Results showed that tubercles provided additional lift for post-stall conditions at low Reynolds number, but only had detrimental effects on the lift and drag generated at high Reynolds number.